Effect of footplate neuromuscular electrical stimulation on functional and quality‐of‐life parameters in patients with peripheral artery disease: pilot, and subsequent randomized clinical trial. Issue 4 (7th January 2020) - Babber, A.; Ravikumar, R.; Onida, S.; Lane, T. R. A.; Davies, A. H.
Abstract : Background: Supervised exercise programmes for intermittent claudication have poor access and limited compliance. Neuromuscular electrical stimulation (NMES) may be an effective alternative. A proof‐of‐concept study and RCT were conducted. Methods: In study 1, eligible patients underwent baseline assessment; treadmill testing for initial (ICD) and maximum (MCD) claudication distance; EuroQoL Five Dimensions five‐level instrument (EQ‐5D‐5L™) and Intermittent Claudication Questionnaire (ICQ) assessment; and measurement of ultrasound haemodynamics of the superficial femoral artery. After familiarization with the NMES device, participants underwent a 30‐min session of stimulation with concomitant recording of haemodynamic measures at 15 min, and after device cessation. Measurements were repeated after 6 weeks of daily use of NMES. In study 2, consecutive patients underwent baseline assessment before online randomization to a supervised exercise programme only, or adjunctive NMES treatment for 6 weeks, followed by repeat measurements. Results: Study 1 (20 patients) showed a significant improvement in MCD (46 per cent; P  < 0·001) and ICD (71 per cent; P  < 0·001). The RCT (42 patients) showed a significant adjunctive benefit of NMES in ICD (46 per cent; P  = 0·014). Improvements were seen in the ICQ (9 points; P  = 0·009) and EQ‐5D‐5L™ ( P  = 0·007) in study 1, and there was a significant adjunctive benefit of NMES on the ICQ score in patients who did supervised exercise (11·2 points; P  = 0·031). Blood volume flow and time‐adjusted mean velocity increased significantly with the device on ( P  < 0·050). Overall, NMES compliance exceeded 95 per cent. Conclusion: Footplate NMES significantly improved walking distance in patients with intermittent claudication when used independently and also as an adjunct to supervised exercise. Registration number: trial 1, NCT02436200; trial 2, NCT02429310 (http://www.clinicaltrials.gov ). Abstract : This article reports a pilot study and subsequent RCT assessing the value of a footplate neuromuscular electrical device in the management of patients with peripheral artery disease. This technology provided both functional and quality‐of‐life improvements in patients with intermittent claudication. Promising technology Abstract : Antecedentes: Los programas de ejercicio supervisado ( supervised exercise programmes, SEP) para la claudicación intermitente ( intermittent claudication, IC) tienen un acceso y un cumplimiento deficientes. La estimulación eléctrica neuromuscular ( neuromuscular electrical stimulation, NMES) puede ser una alternativa clínicamente efectiva. Se realizó un estudio de prueba de concepto y un ensayo controlado aleatorizado. Métodos: Estudio 1: Veinte pacientes elegibles se sometieron a una evaluación inicial que incluía una prueba en la cinta de correr para la distancia inicial de claudicación ( initial claudication distance, ICD) y la distancia máxima de claudicación ( maximum claudication distance, MCD), EuroQoL‐5D (EQ‐5D), valoración mediante el cuestionario de claudicación intermitente (intermittent claudication questionnaire, ICQ), y hemodinámica por ecografía de la arteria femoral superficial. Después de familiarizarse con el dispositivo NMES, los participantes se sometieron a una sesión de estimulación de 30 minutos con el registro concomitante de medidas hemodinámicas a los 15 minutos y después del cese del dispositivo. Se realizaron mediciones repetidas después de 6 semanas de uso diario de NMES. Estudio 2: Se reclutaron 42 pacientes que tras una evaluación inicial y posterior aleatorización al azar en línea, se asignaron al Grupo A, utilizando SEP solamente; o al el Grupo B, con tratamiento NMES complementario durante 6 semanas seguido de medidas repetidas. Resultados: El estudio 1 mostró una mejoría significativa de la MCD (46%, P < 0, 0001) y de la ICD (71%, P < 0.004). El ensayo clínico mostró un beneficio coadyuvante significativo de NMES en la ICD (46%, P = 0, 014). Se observaron mejorías en la puntuación del ICQ (9 puntos, P < 0, 01) y del EQ‐5D ( P < 0, 05) en el estudio 1, con un beneficio coadyuvante significativo de NMES en la puntuación del ICQ (11 puntos, P < 0, 05). El flujo de volumen de sangre (CC/min) y TAMV (cm/s) aumentaron significativamente con el dispositivo en funcionamiento ( P < 0, 05). El cumplimiento global de la NMES superó el 95%. Conclusión: La plataforma de NMES para el pie mejora significativamente las distancias de caminar en la claudicación intermitente cuando se usa de forma independiente y también proporciona un beneficio complementario al ejercicio supervisado en la distancia caminada sin dolor. La mejora del flujo sanguíneo puede ser un mecanismo para explicar estos resultados.